Anatomo-Histological Structure of Ovaries in Postnatal Ontogenesis of Goats - Mallayev Muhriddin G‘ofur o‘g‘li (Scientific Trends, 2024)
The article analyzes the anatomo-histological characteristics of ovaries of goats of different ages. In newborn goats, this allows us to conclude that the organs are divided into the skin and the pulp.
Keywords: Postnatal ontogeny, cube, ovary, follicle, goat.